Repeatability and genotypic stability of agronomic characteristics in Panicum maximum Jacq. - Ferreira, Mariane Rodrigues [UNESP]; Martuscello, Janina Azevedo; Santos Braz, Thiago Gomes dos; Nascimento, Artur Amaral; Jank, Liana; Assis, Juliana Aparecida de; Almeida, Otavio Goulart de; Reis, Gabriel de Assis; Santos, Marcia Vitoria; Santos, Mateus Figueiredo (Inst Investigaciones Agropecuarias, 2019)
In experiments with selection of perennial plants, the initial performance is expected to be maintained throughout the productive life. The probability of repeating the agronomic response can be evaluated by the repeatability coefficient. The objective was to estimate repeatability coefficients of agronomic characteristics in Panicum maximum Jacq. using different methods and identify the best combinations between harvests according to the genotypic stabilization. Seventeen genotypes were evaluated in a randomized complete block design with three replicates. The coefficients of repeatability were estimated by the methods: ANOVA, structural analysis based on the mean of the correlation coefficients (SACOR), analysis of principal components based on the covariance matrix (PCCOV) and correlation matrix (PCCOR). In the genotypic stabilization, coefficients estimated by ANOVA and PCCOR were used. For total DM, repeatability coefficients ranged from 0.3500 to 0.4300 by the ANOVA and PCCOR methods, respectively. High repeatability coefficients were found for the characteristic leaf DM, while low coefficients were observed for leaf and stem percentages and leaf:stem ratio. For the genotypic stabilization of total DM and leaf:stem ratio, the best coefficients were observed for the combination of harvests 5 to 8. There are variations in the estimate of repeatability by different methods and the highest coefficients were those of the principal components based on the correlation and covariance matrices. For the genotypic stabilization, the best coefficients of repeatability and determination were observed for the harvests performed in the second rainy period.
Keywords: Forage; leaf:stem ratio; repeated measures